Peran Dinas Tata Kota Bandar Lampung Dalam Pengendalian Pemanfaatan Tata Ruang - Ati Yuniati (Fiat Justisia: Jurnal Ilmu Hukum, 2012)
The purpose of this study was to determine the role of city planning office of Bandar lampung in Spatial Utilization Control. This study uses empirical and normative juridical approach. Based on this research, the role of city planning office of Bandar lampung in controlling the spatial utilization is to supervise and control the utilization of space. Control of spatial utilization conducted city planning office of Bandar lampung at this time is good enough to carry out the duties and functions of city planning office as has set in the Bandar Lampung Mayor Regulation No. 17 of 2008 on Duties, Functions and Administration of the City Planning Office Bandar Lampung. Key words: role, control, utilization, spatial.